2010
DOI: 10.4049/jimmunol.0902168
|View full text |Cite
|
Sign up to set email alerts
|

CD8 T Cell Cross-Reactivity Networks Mediate Heterologous Immunity in Human EBV and Murine Vaccinia Virus Infections

Abstract: Here we demonstrate complex networks of CD8 T-cell cross-reactivities between influenza A virus (IAV) and Epstein- Barr virus (EBV) in humans and between lymphocytic choriomeningitis virus (LCMV) and vaccinia virus (VV) in mice. We also show directly that cross-reactive T-cells mediate protective heterologous immunity in mice. Subsets of T-cell populations reactive with one epitope cross-reacted with either of several other epitopes encoded by the same or the heterologous virus. Human T-cells specific to EBV-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
135
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(139 citation statements)
references
References 51 publications
(110 reference statements)
4
135
0
Order By: Relevance
“…In HSV-seropositive humans, the memory CD8 ϩ T cells mature during childhood after exposure to other viruses and other pathogens, and the T-cell repertoire that develops cross-reacts with different viruses, including members of the same (or different) herpesvirus family (62)(63)(64)(65). However, this is unlikely for the three VP13/14 epitopes identified in this study because (i) the sequences of the VP13/14 286 -294 , VP13/14 504 -512 , and VP13/14 544 -552 epitopes are highly conserved between HSV-1 strains (100%) and HSV-2 strains (88%) (see Table S1 in the supplemental material); (ii) no significant homology exists between the amino acid sequences of these three epitopes and the VP13/14 amino acid sequences of varicella-zoster virus (VZV; 44% to 55%) and cytomegalovirus (CMV; 44% to 55%) strains (Table S1); (iii) the sequence alignments with published sequences of VP13/14 proteins from other human herpesviruses (e.g., VZV and CMV) did not reveal significant homol-ogies that might be translated to functional cross-reactive T cells (Table S1); and (iv) the three HLA-A*02:01-restricted VP13/14 epitopes reported here to be recognized by CD8 ϩ T cells from HLA-A*02:01-positive, HSV-1-seropositive individuals are also recognized with the same magnitude and breadth by CD8 ϩ T cells developed in laboratory HLA-A*02:01 Tg mice that are selectively bred in sanitized environments and infected with HSV-1.…”
Section: Discussionmentioning
confidence: 99%
“…In HSV-seropositive humans, the memory CD8 ϩ T cells mature during childhood after exposure to other viruses and other pathogens, and the T-cell repertoire that develops cross-reacts with different viruses, including members of the same (or different) herpesvirus family (62)(63)(64)(65). However, this is unlikely for the three VP13/14 epitopes identified in this study because (i) the sequences of the VP13/14 286 -294 , VP13/14 504 -512 , and VP13/14 544 -552 epitopes are highly conserved between HSV-1 strains (100%) and HSV-2 strains (88%) (see Table S1 in the supplemental material); (ii) no significant homology exists between the amino acid sequences of these three epitopes and the VP13/14 amino acid sequences of varicella-zoster virus (VZV; 44% to 55%) and cytomegalovirus (CMV; 44% to 55%) strains (Table S1); (iii) the sequence alignments with published sequences of VP13/14 proteins from other human herpesviruses (e.g., VZV and CMV) did not reveal significant homol-ogies that might be translated to functional cross-reactive T cells (Table S1); and (iv) the three HLA-A*02:01-restricted VP13/14 epitopes reported here to be recognized by CD8 ϩ T cells from HLA-A*02:01-positive, HSV-1-seropositive individuals are also recognized with the same magnitude and breadth by CD8 ϩ T cells developed in laboratory HLA-A*02:01 Tg mice that are selectively bred in sanitized environments and infected with HSV-1.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 These responses were activated and proliferated during severe infections like acute infectious mononucleosis (IM) or influenza A infection. Unique EBV/IAV crossreactive populations have been identified in different HLA-A2+ patient populations, suggesting that crossreactive patterns may be predicted during human infections (Supplementary Figure 2).…”
Section: Translation Into Human Infectionsmentioning
confidence: 99%
“…LCMV and VACV share a complex matrix of CD8 T cell crossreactivity, which has been defined and studied molecularly. 28,52,57 Herein, adoptive transfer studies showed that T cell private specificity of crossreactive memory responses plays a major role in the protection and immunopathology. 32,33 The IAV+LCMV respiratory infection mouse model is noteworthy in that there are both higher titers of LCMV and much greater lung pathology in mice previously infected with IAV, both detrimental effects of heterologous immunity.…”
Section: Heterologous Immunity and T Cell Crossreactivitymentioning
confidence: 99%
See 2 more Smart Citations